Ageing unequally in Europe. (3rd December 2020) - Olivera, Javier
Abstract: To shed light on the quality of the ageing experience in Europe and its heterogeneity, this study adapts and computes the Active Ageing Index—an index constructed at the country level to monitor ageing quality in Europe—at the individual level. This strategy allows the measuring of inequality in the experience of active ageing and is flexible enough to consider different value judgements in the overall assessment of the quality of life while ageing. The study examines the predictors of this inequality by using regressions with a Gini-recentred influence function. It finds that education plays a very significant role in reducing inequality, though its influence varies across countries. Furthermore, the study uncovers large variance in the quality of the ageing experience across Europe. For instance, more than 50% of the populations of Romania, Lithuania and Bulgaria show a level of active ageing quality lower than that of the bottom decile of the distribution in Sweden.